Handbook of research on advanced computational techniques for simulation-based engineering - Samui, Pijush (Advances in computer and electrical engineering (ACEE) book series, 2016)
This book presents the latest scholarly research on the application of computational models to improve the quality of engineering design, featuring extensive coverage on a range of topics from various engineering disciplines.